Risk Factor Analysis of Leprosy Incidence in Coastal Areas: A Review - Devi Savitri Effendy; Tiara Muslimah Jamal; Salfitriana Rebecha Lakawa (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Leprosy, also known as Morbus Hansen (MH), remains a significant public health challenge worldwide, affecting both medical and social aspects of patients’ lives. One of the major barriers to effective management is the persistent stigma experienced by individuals living with the disease. According to the World Health Organization (WHO), Southeast Asia ranks third globally in the number of leprosy cases, reporting a total of 148,495 cases. Indonesia holds the third-highest incidence rate of leprosy in the world. Several risk factors are associated with leprosy transmission, including household contact, social interaction with infected individuals, poor personal hygiene, low health literacy, gender, BCG vaccination status, and socio-economic conditions. Objective: This literature review aims to analyze the risk factors contributing to leprosy incidence in coastal communities. Method: This study employs a qualitative approach using a literature review methodology. A total of 20 national and international peer-reviewed articles published between 2015 and 2025 were selected using keywords such as “Risk Factors for Leprosy Incidence in Coastal Areas,” from databases including Google Scholar, ResearchGate, and PubMed. The selected literature includes studies conducted in Indonesia, the United States, India, Sri Lanka, Kenya, the Netherlands, and Brazil. The data were then compared and analyzed thematically to draw conclusions. Results: The review identifies multiple risk factors contributing to the incidence of leprosy in coastal areas. These include environmental conditions such as high population density, poor housing structures, inadequate ventilation and lighting, and substandard sanitation. Personal hygiene and household crowding were also found to be significant contributors. In addition, socio-economic factors, including low income and limited access to healthcare and nutrition, were frequently reported. Cultural beliefs and misconceptions about the disease, as well as gaps in the implementation of national leprosy control policies, including uneven distribution of health workers and lack of public education, further exacerbate the situation. Conclusion: Leprosy in coastal communities is influenced by a combination of environmental, social, and economic factors. Conditions such as overcrowding, poor ventilation, inadequate sanitation, and low health literacy increase the risk of transmission. Addressing these issues requires a comprehensive and multisectoral approach, including improvements in housing and sanitation infrastructure, targeted health education, equitable distribution of healthcare resources, and strengthened public health policies to reduce the incidence of leprosy in coastal regions. Keywords: Leprosy, Risk Factors, Coastal Communities, Sanitation, Health Inequity.